dx | dx | (1−cos 2x)2 dx | ||||
d) ∫ | , e) ∫ | , f) ∫ | , | |||
1+3cos x | sinx (cosx)3 | (1+cos 2x)3 |
dx | dx | |||
g) ∫ | , h) ∫ | |||
1+(sin x)2 | 5−4sin x +cosx |
−dt | ||
Mamy wtedy: ∫ | = ... | |
(1 − t2)t3 |
1 | 1 − t2 + t2 | 1 | 1 | ||||
= | = | + | = | ||||
(1 − t2)t3 | (1 − t2)t3 | t3 | (1 − t2)t |
1 | 1 − t2 + t2 | 1 | 1 | t | ||||||
= | + | = | + | + | ||||||
t3 | (1 − t2)t | t3 | t | 1 − t2 |
4sin4x | sin4x | |||
... = | = | |||
8cos6x | 2cos6x |
sin2x + cos2x | sinx | 1 | ||||
= ∫ | dx = ∫ | dx + ∫ | dx = | |||
sinxcos3x | cos3x | sinxcosx |
tgx | 1 | |||
= ∫ | + 2∫ | dx | ||
cos2x | sin2x |
1 | (tgx)4 | 1 | ||||
= | ∫ | dx = .... podstawienie: tgx = t , | dx = dt .... | |||
2 | cos2x | cos2x |
1 | ||
= | ∫t4dt | |
2 |